Nonprofit–Public Collaborations: Understanding Governance Dynamics. (August 2015) - Cornforth, Chris; Hayes, John Paul; Vangen, Siv
As many of the challenges facing society are too complex to be addressed by single organizations working alone, nonprofit organizations are increasingly working in collaboration with public authorities. The governance of nonprofit–public collaborations is important for their effectiveness, yet it remains poorly understood. Drawing on case study research, this article examines and develops an extant conceptual model developed by Takahashi and Smutny that seeks to explain the formation and demise of nonprofit collaborations in terms of "collaborative windows" and the inability to adapt initial governance structures. The research finds that while initial governance structures are an important constraint on development, they can be adapted and changed. It also suggests that the development of collaborations is not only influenced by changes in the collaborative window but also by how key actors in the collaboration respond to important internal tensions.